MODELING OF GEOPHYSICAL SIGNALS BASED ON THE SPLINE METHOD (International conference on multidisciplinary science, 2025)
Geophysics is a science that studies the physical properties and processes of the Earth, allowing us to understand and use natural phenomena in practice. Geophysical signals are the result of physical processes in the Earth's interior and exterior and through them [2] . Analysis and modeling of these signals play an important role in oil and gas exploration, natural disaster forecasting, and environmental monitoring. The use of the spline method in processing geophysical signals provides high accuracy and efficiency [5]. Spline-based modeling is an urgent approach for modern geophysical research. Developments in this direction expand the possibilities of searching for natural resources and predicting hazards. This work aims to analyze the process of restoring geophysical signals using the spline method and evaluate the error of the spline. First, we begin the work with the following analytical function selection process